Distinctive Language of Gender in Food Reviewer "Duo Pengacara": A Socio-stylistic Approach - Afidatul Amaliyah, Ayu; Widya Erwanda, Yusandra; Azzahra Aulia, Hedi; Maya Ocktarani, Yesika (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
Gender roles can influence the language style acquired by each individual. Both men and women have their language styles.  The language style used by men tends to be more objective based on logic, while women use words that tend to be expressive according to their feelings.  This article discusses the language style used by food review content presenters on the YouTube channel "Duo Pengacara", which aims to reveal the differences in language styles between female and male presenters.  The author compares two videos containing the content of wives and husbands as object sources.  This research uses a pragmatic stylistic theory approach in gender-based sociolinguistic studies to examine differences in language styles found in video interactions.  The method used is descriptive qualitative by explaining each finding and then comparing the differences in language styles.  The research results showed 43 types of language use styles, which were categorized based on five language styles.  The findings of this research show that the language styles between women and men in the Duo Pengacara food review video object are in coresponding with previous research which assumes that women tend to involve feelings, suportif, and long winded  and men are more realistic, informative and to the point  in their arguments.